1993
DOI: 10.1017/s026505170000142x
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation of Secondary Music Teachers in New South Wales: Is it out of step?

Abstract: This article grew out of a study of four preservice teacher education courses available in New South Wales for the secondary music specialist. Although the secondary syllabuses prescribe an integration of the activities of performing, composing and listening, tertiary teacher education courses are for the most part are based on the conservatoire model that compartmentalises aural, performing and musicology studies and almost entirely neglects composition. There also appears to be a lack of knowledge of and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Crucially, the underlying hypothesis of the model is that the disparity between the individual's capability and strategic beliefs is the most significant influence on subsequent academic performance. In an exploratory study with a group of music education students this was found to the case (Jeanneret, 1993). This was replicated in an exploratory study with music students in the area of solo performance (Hewitt, 2003).…”
mentioning
confidence: 79%
“…Crucially, the underlying hypothesis of the model is that the disparity between the individual's capability and strategic beliefs is the most significant influence on subsequent academic performance. In an exploratory study with a group of music education students this was found to the case (Jeanneret, 1993). This was replicated in an exploratory study with music students in the area of solo performance (Hewitt, 2003).…”
mentioning
confidence: 79%
“…The importance of practicum in building the confidence of PSMTs is also evident in numerous studies (Brand, 1982;Jeanneret, 1993;Kelly, 2015;Schleuter, 1991;Turney, 1977). PSMTs in NSW institutions typically complete four practicums across their 4 years of tertiary education: a primary school practicum at the end of the first year, then secondary practicums in their second and third years, and concluding with an extended practicum in their fourth and final year.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Internationally, a significant body of research has investigated the influences on music teachers’ choice of careers, with a strong focus on preservice teachers and early career teachers. In Australia, research has explored the effectiveness of preservice music education programs and the reasons students choose to become music teachers (Ballantyne & Packer, 2004; Jeanneret, 1993; Rowley, 2012; Rowley & Dunbar-Hall, 2012; Swainston & Jeanneret, 2013); their preparedness for their teaching careers (Ballantyne, 2007; Rowley, 2010); and their emerging teacher identities (Ballantyne et al, 2012; Ballantyne & Grootenboer, 2012). Considerable research has also emerged from America (Bergee & Demorest, 2003; Isbell, 2008; Parkes & Jones, 2012; Pellegrino, 2015; Sichivitsa, 2007) and England (Mills, 2005; Odena & Welch, 2007; Welch et al, 2011), where the school music education systems and college preparation are quite different from the NSW experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However ideal, many teachers faced problems enacting these models (Burke, 2014), with the rigidities of timetabling and assessment often imposing a degree of separation, and prioritisation of one learning activity over another (Jeanneret, 1993). The construction of musical knowledge also posed a problem, as knowledge outcomes were not articulated clearly nor mapped out in sequence by curriculum writers at the time (Secondary School Board, 1981, 1986.…”
Section: Theoretical Framework: Legitimation Code Theory (Lct)mentioning
confidence: 99%
“…As with the earlier pre-reform syllabus, learning was still expected to occur in sequence and then 'aural experience be symbolised through some form of notation' (Secondary School Board, 1986, p. iii). However, without clear expectations or skill outcomes for each stage of learning and the removal of official examinations at the junior secondary level, the design of teaching programmes from school to school proved a challenge for many teachers whose learning was solely defined by the previous élite code passage (Jeanneret, 1993). Moreover, as the framework was intended for use in conjunction with systems of music notation, a disparity prevailed between a range terminology, symbols and their potential meanings, with the recording assuming only a secondary authority in teaching and learning interactions.…”
Section: Theoretical Framework: Legitimation Code Theory (Lct)mentioning
confidence: 99%